A botanical perspective on the Portuguese crown jewels – the golden fleece insignia - Carvalho, Luis; Barros, Margarida; Fernandes, Mariana; Fernandes, Francisca Maria (Ethnobotany Research and Applications, 2025)
The Royal Treasury Museum (Lisbon) houses one of the richest collections of jewels in Europe and its collection of circa one thousand pieces, includes many that depict stylized plants. Studying them provides us with an insight into the symbolic use of plants in the societies that created them and reveals their links with the classical symbolic codes. A very precious jewel in the collection is the insignia of the Order of the Golden Fleece, made in the early years of the 19th century, with 1,741 diamonds (more than 300 carats), 190 rubies and one sapphire, arranged in the shape of palm leaves, laurel branches and oak fruits, whose symbolism alludes, not only the Portuguese Royalty, but to the Greco-Roman civilization and to the Christian doctrine.